Strength profile in wrestlers - a systematic review - Baic, M.; Trajkovic, N..; Ðordevic, D.; Stankovic, M.; Pekas, D. (Archives of Budo, 2022)
Background and Study Aim: Succes in wrestling depends on many different factors, but strength could be considered as the most important one. Different strength indicators are closely related to high-level wrestling performance. The aim of this review is to generalize the recommendations of the authors of works dedicated to the analysis of muscle strength in wrestlers, regardless of style (Greco-Roman and freestyle) and knowledge of the most commonly used tests to assess the various manifestations of this motor ability.